ANALISIS KEMAMPUAN MEMAHAMI BACAAN PADA SISWA KELAS III SEOLAH DASAR - Gea, Gea Alviodita; Romadon; Sasih Karnita Arafatun (Universitas Muhammadiyah Bangka Belitung, 2023)
This research is motivated by students' reading comprehension skills. The research objective was to determine the reading comprehension ability of third grade students in the Fishermen 1 Sungailiat environment. This study uses a descriptive qualitative method which is carried out by seeking information related to the problem, explaining the objectives to be achieved, planning the form of the approach, and collecting data or results as a research report. Based on the results of this study in the Sungailiat 1 fishermen's environment with a sample of 5 people, 3 people were very good at reading comprehension, while 2 people were included in the adequate category in reading comprehension. is enough. Solutions that can be applied if students' understanding of reading wants to increase, students can be given more practice questions whose answers use student reasoning, because this will affect students' ability to read